2017
DOI: 10.4236/ojped.2017.74029
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age, Low Birth Weight and Early Neonatal Death in Tertiary Hospital in the Volta Region of Ghana

Abstract: Objectives: Current study sought to determine an association between Low Birth Weight (LBW) and early neonatal mortality at a resource limited country's referral hospital and to determine relationship between maternal age and birth outcomes. Method: A retrospective study analyzing data on births in the Volta Regional Hospital, Ghana from the period of November 2011 to June 2016. A total of 8279 births were analyzed. Results: Results suggest that teenage mothers (8.60%) are more likely to give birth to pre-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
(15 reference statements)
2
6
0
Order By: Relevance
“…We found that nearly 10% of the infants born within the study period had birth weights below 2.5kg (LBW). Further analysis revealed that the odds LBW were higher among babies born to teenage mothers (age less than 20 years) and low among babies of mothers older than 30 years albeit not significant, which agrees well with several other studies [23, 2733] including findings of the 2010 Ghana Demographic and Health Survey [4]. This may be due to poor socioeconomic status, maternal malnutrition, and inadequate antenatal care of teenage mothers as these factors have been reported to influence birth weight of babies born to teenage mothers in low-and-middle-income countries [3436].…”
Section: Discussionsupporting
confidence: 92%
“…We found that nearly 10% of the infants born within the study period had birth weights below 2.5kg (LBW). Further analysis revealed that the odds LBW were higher among babies born to teenage mothers (age less than 20 years) and low among babies of mothers older than 30 years albeit not significant, which agrees well with several other studies [23, 2733] including findings of the 2010 Ghana Demographic and Health Survey [4]. This may be due to poor socioeconomic status, maternal malnutrition, and inadequate antenatal care of teenage mothers as these factors have been reported to influence birth weight of babies born to teenage mothers in low-and-middle-income countries [3436].…”
Section: Discussionsupporting
confidence: 92%
“…As the gestational age increases by one week, the newborn is more likely to survive during the early neonatal period. This finding corresponds well with studies conducted in Ethiopia (Gondar, Addis Ababa, Jimma, Durame, and Mekelle) [ 62 67 ], Ghana [ 68 ], China [ 27 ], and Brazil [ 69 ]. The possible reason might be the fact that gestational age is strongly related to fetal maturity.…”
Section: Discussionsupporting
confidence: 91%
“…Further, a study by Afeke et al (17) examined 8,279 delivery records from the pediatrics unit of the Volta Regional Hospital spanning the time periods November 2011 to June 2016 ( 17 ). Low birthweight in the sample was 10.7%; the study showed that preterm babies had a 4% chance of survival within 7 days of birth compared to the 96% survival rate for term babies ( 17 ). Moreover, a prospective cohort study conducted at the Kinatampo Health Research center serving 4 district hospitals and 69 health facilities investigated neonatal mortality in a sample of 22, 906 records ( 18 ).…”
Section: Introductionmentioning
confidence: 99%